Pemanfaatan Teknologi Scispace untuk Meningkatkan Layanan Literature Review di Perpustakaan - Dewi, Sarwendah Puspita; Irawati, Indira (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2024)
Library information services utilizing artificial intelligence (AI)-based technology, such as literature review services that are closely related to the process of searching and finding reading sources or scientific information, are becoming very relevant today. In Indonesia, one of the libraries that has implemented AI-based technology in its literature review service is the BRIN Library. Scispace, an AI-powered platform used to simplify the process of understanding scientific papers, has been utilized by the BRIN Library since November 2023. Scispace is interesting to study because its potential has not been widely explored. Based on this review, this study aims to examine the role of Scispace in supporting literature review services in libraries. The benefit of this study is to provide an overview of the optimization of literature review services using Scispace technology at the BRIN Library, both its advantages and disadvantages. The scope of this study object is the BRIN Library, a special library under the auspices of the National Research and Innovation Agency (BRIN) which is the parent of all researchers on a national scale. The research was conducted using a qualitative approach in the form of document analysis, observation and interviews. The documents analyzed were the business process (SOP) of Literature Review Services at the BRIN Library. Observations and interviews were conducted with two librarians who have capacity in the field of information services at the BRIN Library. The results of the study indicate that Scispace is able to accommodate the needs of literature review services in a library, especially in the stages of searching and selecting literature. Abstraction, acceleration (speeding up) time, and accuracy are the advantages obtained from utilizing Scispace. In addition, Scispace also has shortcomings although not too fundamental, such as the import feature in the reference manager feature (Zotero) which was ineffective when operated using a shared account. Thus, the Scispace technology is very possible to be utilized by library managers to support their literature review services, especially special libraries and universities with users who are very close to research activities and writing scientific articles.